If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18a + 3 = 0 Reorder the terms: 3 + 18a = 0 Solving 3 + 18a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 18a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 18a = 0 + -3 18a = 0 + -3 Combine like terms: 0 + -3 = -3 18a = -3 Divide each side by '18'. a = -0.1666666667 Simplifying a = -0.1666666667
| 0.5y^3=13.5 | | 56=-13 | | 15x-20=70 | | X+4=28-x | | x(3x-15)=0 | | -7x+5=-x-1 | | 5-0.8(d-18)=0.4(12d-18) | | 3-3x=x+47 | | 81x^2=126x-49 | | (x+9)(x-1)= | | 2x+7=-3+5x | | 5x+15=3x+8+2x-7 | | 3y-13+2y-12=180 | | 2t-83+2t-51=180 | | 14y-6=5 | | 5x-2=-x-32 | | -3r+20=15r-8 | | 11x+11+9x-11=180 | | 2t-51+2t-83=180 | | 11x+11+2y-12=180 | | 6x-7=53-4x | | 8x+4y=52 | | 2x+7=8(4+x) | | 2q-88+q+58=180 | | 2x+7=8(4+6) | | 0.3(n+4)=5 | | 90=6x-1 | | -3+4x=3x-15 | | -8+4x=6x+0 | | -4-2x-5x=80 | | 4u-42=-2(u-3) | | 6-3(1+8k)=33 |